DEVELOPMENT OF NATIONAL SELF-AWARENESS OF EDUCATION ACQUISITIONS MEANS OF THE TECHNOLOGY OF MANUFACTURING A DOLL-MOTANKA - КИРИЧЕНКО , Р.В.; ОЛІЙНИК , Д.В.; ТИМЧЕНКО , А.А. (Fashion Industry, 2024)
Тhe purpose. To justify and develop a method of conducting an educational class with elements of a master class with students of education on the technology of making a doll-motanka. Methodology. Analysis of psychological and pedagogical literature, synthesis, comparison, interview, survey, generalization and systematization of the obtained results. Results. On the basis of the research of the historical significance of the motanka doll for the Ukrainian people, an educational class was developed and conducted with elements of a master class on making a motanka doll for students of the communal institution of professional (vocational and technical) education "Kyiv Professional College of Technology and Fashion Design". The analysis of the survey showed that the formation of students' ideas about Ukrainian culture, the revival and creation of the national cultural and historical traditions of the Ukrainian people, familiarizing students with the history of national toys of Ukrainian culture, mastering the basics of the art of making a folk doll, the consistent implementation of operations of project and technological activity from the idea before its implementation in a finished form, influences the development of national self-awareness among modern youth, increases interest in their ethnography and cultural heritage. The peculiarities of the use of doll therapy during the war have been determined. Investigating the problem of forming the foundations of national self-awareness in students, it was concluded that this is a complex formation of the psyche, which gives the opportunity to feel and realize the essence of one's national identity, one's place among other nations and peoples of the world, the feeling and awareness of pride for belonging to one's nation. Scientific novelty. The possibilities of the art of making dolls as art therapy during the war have been determined. Practical value. The results of the work can be used by teachers of professional (vocational and technical) education institutions for the formation of value orientations and the establishment of the national and patriotic consciousness of young people.